Vitis vinifera Production in Michigan: Factors and Trends Driving Cultivation Patterns - Bunting, Erin L.; Wanyama, Dan; Goodwin, Robert; Weil, Nicholas; Sabbatini, Paolo; Andresen, Jeff (Frontiers in Plant Science, 2021)
Vinifera cultivation is a thriving and growing industry across the state of Michigan (MI), USA. Extensive time, funds, and effort have been applied by the industry to promote growth and the onset of new producers. Specifically, Vitis vinifera wine grapes, which have been cultivated in MI since the 1970s, have seen a rapid expansion and investment from both first-time and legacy growers. However, historically, MI’s climate presented a challenge for cultivation due to low growing season temperatures, short growing seasons, and excessive precipitation at the time of harvest. Over time, two key factors have led the MI wine industry to overcome the challenging climate. First, as seen in the literature, there are noted changes in climate, especially since the late 1980s, leading to more favorable conditions for cultivation. Second, MI growers traditionally focused on Vitis vinifera cultivation, which is susceptible to low winter temperatures, selected less vulnerable regions within the state while also focusing on vine protection techniques. Given the rapid growth of the wine industry across MI, there is a need to understand suitability and its drivers to help all growers make economically impactful decisions on production and expansion of wine grapes. This article looked to study the suitability of MI vinifera across the state in two ways. Initially, through an extensive literature review, the key drivers and commonly noted trends guiding vinifera production were chronicled. Second, through a trend analysis of the key drivers of suitability, the study investigated how such variables are changing, significantly, over space and time. Results of this work expand our knowledge of cool climate agriculture production and suitability for cultivation and highlights the complexity of relating suitability drivers for non-cool climate to cool climate vinifera cultivation.